PENERAPAN MODEL GAME BASED LEARNING BERBANTUAN MEDIA BLOOKET UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV SDN 166 LABURAWUNG KECAMATAN LALABATA KABUPATEN SOPPENG - vera ferisca; rosmalah; rukayah (MACCA : Science-Edu Journal, 2026)
This research is a classroom action research (CAR) that aims to determine the application of the Blooket-assisted game-based learning model to improve the Indonesian language learning outcomes of fourth-grade students at SDN 166 Laburawung, Lalabata District, Soppeng Regency. The subjects in this study were all 25 fourth-grade students and the fourth-grade homeroom teacher. Data collection techniques used observation and tests. Data analysis techniques in this study included data reduction, data presentation, and drawing conclusions. The results showed that the percentage of teacher activity in cycle I reached the Fair (C) category and in cycle II increased to the Good (B) category. The study shows that the Indonesian language learning outcomes of students in cycle I were 66,66% or 16 students obtained an average score of 70,20 with a sufficient (C) qualification and increased in cycle II by 83.33% or 20 students with an average score of 80.20 with a good (B) qualification. It can be concluded that the Blooket media-assisted Game-Based Learning model can improve Indonesian language learning outcomes.